Dissemination of AI Utilization to Elementary School Teachers towards the Realization of STEM Class - Murein Miksa Mardhia; Dwi Normawati; Risanti Dhaniaputri; Fiorella Fiorella Adistya Moniaga; Aisyah Dwi Puspita; Yogya Rusydi Arifin; Muhammad Musthofa Masyhur; Haura Nidaulhaq; Dhea Aprilia Ayu (Universitas Ahmad Dahlan, 2026)
Background: The rapid advancement of science and technology requires elementary school students to develop core competencies in Science, Technology, Engineering and Mathematics (STEM), along with early digital literacy. However, STEM implementation in primary education remains limited due to inadequate infrastructure, disparities in teacher competence, and minimal exposure to emerging technologies such as Artificial Intelligence (AI). Contribution: This program introduces an integrated training framework that simultaneously combines STEM learning, computational thinking, and practical AI applications for elementary school teachers. Method: An evaluative approach with a quantitative descriptive design was employed. The program was conducted in three stages: preparation, training, and evaluation. The preparation stage involved needs analysis through classroom observations and interviews. The training stage consisted of two intensive sessions covering computational thinking, basic coding using Scratch, generative AI, AI ethics, and prompt engineering. Results: The results demonstrate a measurable improvement in teachers’ competencies, with the average percentage score increasing from 66% to 84%. The most significant improvements were observed in algorithmic understanding, computational thinking, ethical awareness of AI usage, and the application of digital tools such as Scratch and AI-assisted design platforms. Conclusion: The program effectively enhanced teacher readiness to implement structured STEM learning and demonstrated the potential of integrating AI into teacher professional development at the elementary level.